Images and Voices of Change: Engaging Local Community in Assessing Impact of Millennium Villages Project in their Lives in Sauri Village, Western Kenya - Nyasimi, Mary; Okang’a, Joseph (Consilience, 2009)
The Earth Institute at Columbia University is implementing a development program in ten countries in Sub-Saharan Africa. Referred to as the Millennium Village Project (MVP), the program aims to use a combination of science-based interventions and community participation to transform the livelihoods of African people and ultimately lift them out of extreme poverty. Involvement of local people is a critical ingredient and key processes of empowering them and ensuring the sustainability of MVP. To engage local people in assessing the impact of MVP on their lives, a community led Photovoice project was initiated in the first millennium village-Sauri, Kenya. In this project, local research participants used digital cameras and their own narratives to share their emic view of their changing world. The main objective of this photo essay is to share photographs and narratives from ten local research participants of different ages, educational levels and gender. The photographs and stories indicate that MVP is positively impacting on local people, and it can be used as a monitoring tool for various activities. In addition, the research participants were enthusiastic about Photovoice, and they provided a powerful internal visual interpretation of community changes. All the photographs and their stories will be shared in a community Photovoice exhibition later this year.